CHAQ2020 - Hope Bay - Photographic data - CHAQ2020 - Hope Bay - Panoramas - Westin, Jonathan (University of Gothenburg, 2021)
The first Swedish Antarctic Expedition (1901-1903), led by Otto Nordenskjöld, sailed to Antarctica on the ship Antarctic captained by CA Larsen, and established a research station on Snow Hill Island. There six members overwintered and performed paleontological, meteorological, geomagnetic and geological studies, while the rest of the expedition set sail for South Orkney.

After the winter, on the way back to Snow Hill Island, the Antarctic got stuck in the ice and sank. At this point, the expedition members were divided into three groups. One of these overwintered an extra year on Snow Hill Island, whereas the other two groups were forced to build stone huts in order to overwinter at Hope Bay and Paulet Island. An Argentinean vessel, the Corbeta Uruguay, rescued the expedition in November 1903.

CHAQ 2020 is an Argentinean-Swedish project with fieldwork in the area around the Antarctic Peninsula aiming to investigating and documenting the historical remains of the first Swedish South Polar expedition under the leadership of Otto Nordenskjöld 1901-1903. The material was collected in January and February 2020.

This catalogue entry collects the photographic material and the panoramas from Hope Bay.

The set consist of panoramas obtained from three scanning sessions with the Faro Focus m70 on January 22 and 24, 2020 by Jonathan Westin. The resolution of the panoramas is 20288 x 10144 pixels. Corresponding raw data point clouds in FLS-format for each of the scanning positions can be downloaded from the repository (catalogue entry "CHAQ2020 - Hope Bay - Spatial data").

Syftet med forskningsprojektet var att dokumentera lämningarna efter Otto Nordenskjölds Antarktisexpeditionen 1901-1903. Materialet består av fotografier, planer, ritningar, 3d-modeller och drönarfilmer från Snow Hillön, Hoppets vik och Seymourön.

Denna katalogpost samlar fotografier och panoraman från Hoppets Vik.

Se den engelska beskrivningen för mer information.

Datasetet består av panoramabilderna skapade under två skanningsessioner med en Faro Focus m70 den 22 och 24 januari, 2020 av Jonathan Westin. Upplösningen på bilderna är 20288 x 10144. Högupplösta punktmoln för varje panorama-position finns lagrade i katalogpost "CHAQ2020 - Hoppets vik - Spatiala data".
CHAQ2020 - Hoppets vik - Fotografiska data - CHAQ2020 - Hoppets vik - Panoraman
Keywords: Antarctica; Antarktis; Antarctic region; Adélie penguin (Pygoscelis adeliae); Adéliepingvin (Pygoscelis adeliae); Chinstrap penguin (Pygoscelis antarcticus); Hakremspingvin (Pygoscelis antarcticus); Gentoo penguin (Pygoscelis papua); Åsnepingvin (Pygoscelis papua); Nordenskjöld, Otto, 1869-1928; Nordenskjöld, Otto, 1869-1928; Swedish Antarctic Expedition, 1901-1904; Första svenska Antarktisexpeditionen, 1901-1904; History and Archaeology; Historia och arkeologi